Cross-border loss offset can fuel tax competition - Andreas Haufler; Mohammed Mardan (Center for Economic Studies and ifo Institute (CESifo), 2013)
Following recent court rulings, cross-border loss compensation for multinational firms will likely be introduced, at least in Europe. This paper analyzes the effects of introducing a coordinated cross-border tax relief in a setting where multinational firms choose the size of a risky investment and host countries endogenously choose tax rates. We show that coordinated cross-border loss compensation is likely to intensify tax competition when, following current international practice, the parent firm's home country bases the tax rebate for a loss-making subsidiary on its own tax rate. In equilibrium, tax revenue losses will then be even higher than is implied by the direct effect of the reform. In contrast, tax competition will be mitigated when the home country bases its loss relief on the tax rate in the subsidiary's host country.
Keywords: H32; F23; H25; 330; cross-border loss relief; tax competition; profit shifting; Verlust; Steuerbegünstigung; Außensteuerrecht; Steuerwettbewerb; Multinationales Unternehmen; Theorie; Europa